On the three-dimensional singular stress field near the corner front of revolution-shaped inclusions - Wang, Congman (2022)
Three-dimensional (3D) particles in composite materials often have sharp corners which cause complex stress singularities. In our current research, the 3D singular stress fields in the corner front vicinity of various revolution-shaped inclusions have been investigated using a specially developed novel singular inclusion corner element SICE. Numerical eigensolutions with both singular and non-singular terms for the 3D singular stress and displacement fields in the curvilinear coordinate system are transformed into the interpolation forms of the SICE. The robustness of the element stiffness matrix is reflected in the fact that it is established based on a local coordinate system attached to the rotation axis with arbitrary inclusion orientation. The singular stresses in the vicinities of revolution-shaped inclusions of various shapes, orientations and material properties are investigated. The benchmark examples show that the proposed SICE has excellent versatility and are very useful for micro-damage analysis of particle-reinforced composites.